Comparing the delivery to the hair bulb of two fluorescent molecules of distinct hydrophilicities by different nanoparticles and a serum formulation - Costa, Cristiana (2021)
The follicular route is an important drug penetration pathway in any topical application, either concerning dermatological and cosmetic skin treatments or any transdermal administration regimen. Efficient transport into follicles will depend on drug inherent properties but also on the chosen vehicle. The main study goal was to compare several systems for the delivery to the hair bulb of two fluorescent molecules of different water affinities: the hydrophobic Nile Red and the quite similar but hydrophilic Nile Blue. Three common nanoparticle types were compared in terms of encapsulation efficiency and stability: liposomes, ethosomes and polymeric nanoparticles. A liquid serum-like formulation was also developed, adjusting the final ethanol amount to the type of dye to be solubilized. Then, this formulation and the nanoparticle systems that successfully passed characterization and stability stages were further studied on their ability to reach the bulb. The serum formulation was able to deliver, both drug models, to deeper follicular regions than nanoparticles. Attending to the envisioned zone target of the follicle, the simplest approach proved to be the best choice from all the systems tested in this work. Nonetheless, nanocarriers and the inherent complexity of their manufacturing processes may be justified under very specific requirements.